Textual Features of Lithographic Editions (On the Example of the (Lithographic Version of “Boburnama”) (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the textual features of the lithographic editions of the work Boburnoma from a textological perspective. The study examines the general characteristics of lithographic copies, as well as their orthographic, lexical, and stylistic peculiarities. Special attention is given to the comparative analysis of manuscript and lithographic versions in order to determine their similarities and differences in terms of textual stability, language norms, and editorial interventions.The research demonstrates that lithographic editions reflect the textual state of the work during the late nineteenth and early twentieth centuries and represent an important transitional stage between manuscript tradition and later typographic publications. The orthographic system, preservation of Chagatai language features, use of Arabic and Persian lexical elements, and the retention of the author’s memoir style are analyzed as key textual components. The findings confirm that lithographic copies serve as a significant source for textology, historical linguistics, and literary studies, contributing to the reconstruction of the complete textual history of the work.
Keywords: lithographic edition; Boburnama; textology; orthography; lexicon; stylistics; manuscript; tradition; comparative analysis